Astronomy outreach programs with STEM ambassadors under the C3AOL project - Siti Nur Razira Razali,; Muhammad Ezzat Abdul Hamid,; Nurul Shazana Abdul Hamid,; Marlia Puteh,; Wan Mohd Aimran Wan Mohd Kamil,; Zalita Zainuddin,; Rozidawati Awang,; Mohammad Afiq Dzuan Mohd Azhar,; Mohd Zamri Shah Mastor,; Nurhasmiza Abu Hasan Sazalli,; Othman Zainon,; Nilam Nur Amir Sjarif,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper reports our experiences in conducting outreach astronomy programs involving high school students and the general public. These programs are part of an interdisciplinary research project entitled Cross-cultural Computer supported Collaborative Learning for Student Capacity Building in Multifaceted Competencies through Astronomy Online Labs (C3AOL). As part of this research project, two selected undergraduate Physics students were named as STEM ambassadors and tasked in disseminating astronomical facts and concepts via outreach activities, thus consolidating their knowledge, creativity, and identity as STEM ambassadors. The STEM ambassadors have planned and conducted an Astronomy outreach program with high school students from the Pusat PERMATApintar Negara (currently known as Pusat GENIUS@Pintar Negara), UKM. This was followed by a public stargazing session at the National Planetarium, Kuala Lumpur that involved planetary and lunar eclipse observations. This project provided a valuable opportunity for the STEM ambassadors to convey astronomical knowledge effectively and interestingly in multiple contexts, whether amongst their peers or junior students, or even with the general public. A short-term impact of this project is the diffusion of their knowledge and enthusiasms in Astronomy to high school students as well as the general public through outreach programs such as dialogues session and talks at space centers and experience sharing via social media.